2004
DOI: 10.1111/j.1469-8137.2004.01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Epichloë glyceriae infection affects carbon translocation in the clonal grass Glyceria striata

Abstract: Summary• Systemic fungal endophytes derive resources from hosts and can affect host resource movement and integration. We examined whether infection by Epichloë glyceriae altered clonal growth of its host, Glyceria striata , through changes in physiology.• Growth of severed and intact stolons was compared to examine physiological integration in infected and disinfected (fungicide-treated) plants. To assess whether infection changed carbon (C) movement, labelling with 14 C was used.• We found physiological inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Since the meadow populations of Wne fescues are (Wäli et al 2007), and maternally transmitted symbionts are not suggested to be able to persist in their host populations at high frequency if they are harmful to the host (Law 1985;Frank 1997;Clay 1998), beneWcial eVects of the endophytes in meadow habitats probably occur in later stages of the life cycle of these long-lived perennials. Such beneWts from endophytes may be enhanced seed production, or better tolerance to biotic and abiotic factors (see, e.g., Clay et al 1993;Bazely et al 1997;Pan and Clay 2002;Pan and Clay 2004;Koh and Hik 2007). In addition, the horizontal transmission of fungus may be one possible mechanism maintaining the high infection frequency in meadow populations of Wne fescues as epiphyllous mycelial nets, possibly of Epichloë endophyte, have also been detected in F. rubra and F. ovina (Moy et al 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Since the meadow populations of Wne fescues are (Wäli et al 2007), and maternally transmitted symbionts are not suggested to be able to persist in their host populations at high frequency if they are harmful to the host (Law 1985;Frank 1997;Clay 1998), beneWcial eVects of the endophytes in meadow habitats probably occur in later stages of the life cycle of these long-lived perennials. Such beneWts from endophytes may be enhanced seed production, or better tolerance to biotic and abiotic factors (see, e.g., Clay et al 1993;Bazely et al 1997;Pan and Clay 2002;Pan and Clay 2004;Koh and Hik 2007). In addition, the horizontal transmission of fungus may be one possible mechanism maintaining the high infection frequency in meadow populations of Wne fescues as epiphyllous mycelial nets, possibly of Epichloë endophyte, have also been detected in F. rubra and F. ovina (Moy et al 2000).…”
Section: Discussionmentioning
confidence: 96%
“…All these could increase plant nutrition efficiently, thus favoring the plant's growth and yield (Barretti et al 2008). Pan and Clay (2004) found that 14 C movement from labeled leaves was greater in infected plants than in non-infected plants. Studies on enzyme activities, concentrations of amino acids, and ammonium indicated that the interaction with endophytes significantly alters at least nitrogen metabolism.…”
Section: Relationships Between Endophytes and Their Host Plantsmentioning
confidence: 95%
“…Integration of water and nutrient transport is an important part of physiological integration of clonal plants (Evans, 1992;Landa et al, 1992) and is affected by genetically based physiological factors and morphological structures, but also by environmental conditions (Pan and Clay, 2004;Price and Hutchings, 1992;Wang et al, 2004). In heterogeneous environment, ramets in resource abundant patches will serve as "donors" supplying resources, while ramets in resource poor patches will function as "recipients" obtaining resources.…”
Section: Changes In Intensity Of Physiological Integration In Trifolimentioning
confidence: 97%